(untitled) (Modern education and development, 2025)
This article explores the possibilities of conservative treatment in children diagnosed with dolichosigma, without the need for surgical intervention. The effectiveness of a comprehensive approach was assessed, involving dietary therapy, physiotherapy, pharmacological treatment (prokinetics and laxatives), and rectal procedures. Clinical observations revealed a significant reduction in symptoms such as constipation, bloating, and abdominal pain, alongside an improvement in patients’ quality of life. The results support the feasibility of effective non-surgical management in early-stage dolichosigma, offering a safer and less invasive therapeutic option for pediatric patients